Assessment of the Real Time of Cooling of a 1.5hp Window Unit Air – Conditioner Utilizing Thermometer - Emughiphel Nelson Igoma (IJAEM, 2022)
The study, assessment of the real time of cooling of a 1.5HP Window air conditioner utilizing thermometer has been performed. The investigation took fifteen (15) days during which data were collated utilizing locally improvised materials like thermometer and stopwatch. The experimental data collation was performed in the Morning Hours: 7:00AM – 9:00AM; Afternoon Hours: 12:00PM – 2:00PM and Evening Hours: 4:00PM – 6:00PM respectively and it started from the least 160C and ended with the highest which is 300C. The investigation revealed that for every 10C rise, it will take 1.207% time taken to cool the Office Room during the period of 7:00AM – 9:00AM, 1.119% time taken to cool the Office Room during the period 12:00PM – 2:00PM and 1.186% time taken to cool the Office Room during the period 4:00PM – 6:00PM respectively. Also, it was found that the relative humidity affects the time of cooling adversely thereby causing fluctuation in the certainty of time. It is recommended that cleaning of the filter twice weekly will debar blockage thereby ameliorating the air conditioner performance.
Keywords: Temperature; Relative Humidity; Stopwatch; Time